A model for flexi-bar to evaluate intervertebral disc and muscle forces in exercises. Issue 10 (October 2016) - Abdollahi, Masoud; Nikkhoo, Mohammad; Ashouri, Sajad; Asghari, Mohsen; Parnianpour, Mohamad; Khalaf, Kinda
Highlight: A lumped parameter model was investigated for the FLEXI-BAR, a training instrument that provides vibration stimulation. The model was validated and its accuracy was 8%. The model was implemented in AnyBody, a musculoskeletal modeling software, to simulate the FLEXI-BAR exercises. Different lumbar discs forces, spinal muscles and hand muscles forces were extracted during a FLEXI-BAR exercise. This set-up is able to assess various FLEXI-BAR exercises based on various musculoskeletal forces. Abstract: This study developed and validated a lumped parameter model for the FLEXI-BAR, a popular training instrument that provides vibration stimulation. The model which can be used in conjunction with musculoskeletal-modeling software for quantitative biomechanical analyses, consists of 3 rigid segments, 2 torsional springs, and 2 torsional dashpots. Two different sets of experiments were conducted to determine the model's key parameters including the stiffness of the springs and the damping ratio of the dashpots. In the first set of experiments, the free vibration of the FLEXI-BAR with an initial displacement at its end was considered, while in the second set, forced oscillations of the bar were studied. The properties of the mechanical elements in the lumped parameter model were derived utilizing a non-linear optimization algorithm which minimized the difference between the model's prediction and the experimental data. The results showed that the model is valid (8% error) and can be used for simulating exercises with the FLEXI-BAR for excitations in the range of the natural frequency. The model was then validated in combination with AnyBody musculoskeletal modeling software, where various lumbar disc, spinal muscles and hand muscles forces were determined during different FLEXI-BAR exercise simulations.